Age Differences in Effects of Global Factors on Cultural Identity: An Exploration of Tribal Community Dera Ghazi Khan - Kamran, Muhammad Adeel; Bhutta, Mazhar Hussain; Shamshad, Tahira; Saboor, Abdul (Pakistan Journal of Humanities and Social Sciences, 2023)
The study explored effects of global factors on cultural identity of tribal men in Dera Ghazi Khan. For data collection, twelve tribal men (six young and six old) were interviewed. Through deductive thematic analysis eight themes were formed based on predetermined research questions. The results showed that use of global factors was common and frequent among tribal men. Among global factors, internet was preferred by young tribal men for entertainment while old men preferred radio for news updates and weather forecasts. The tribal people were learning and adopting new languages, different styles in dressing, food and ways of celebration from other cultures. Traditional occupations and leisure time activities were being replaced with modern ones. Attitude towards traditional roles of men and women were in transition. The tribal customs like horse riding, shooting, dancing with swords, dress pattern and Jirga system were being extinct while values like hospitality, cooperation, respect for women and elders still exist. Young tribal people liked to form social relations with people from other cultures while older liked to maintain their relationships with local community members.